Intracellular Organization of Proteins and Nucleic Acids via Biomolecular Condensates in Human Health and Diseases - Raffaella Gallo (MDPI AG, 2023)
Eukaryotic cells are intracellularly divided into several compartments that provide spatiotemporal control over biochemical reactions. Phase separation of proteins and RNA is emerging as an important mechanism underlying the formation of intracellular compartments that are not delimited by membranes. These structures are also known as biomolecular condensates and have been shown to serve a myriad of cellular functions, such as organization of cytoplasm and nucleoplasm, stress response, signal transduction, gene regulation, and immune response. Here, the author will summarize our current understanding of intracellular phase separation, its biological functions, and how this phenomenon is regulated in eukaryotic cells. Additionally, the author will review recent evidence of the role of biomolecular condensates in the development of pathophysiological conditions, with special emphasis on cancer and immune signaling.